Characterizations of Weakly Contra-$(τ_1,τ_2)$-continuous Functions (European Journal of Pure and Applied Mathematics, 2025)
This paper presents a new class of functions called weakly contra-$(τ_1,τ_2)$-continuous functions. Moreover, several characterizations and some properties concerning weakly contra-$(τ_1,τ_2)$-continuous functions are established.
Keywords: $τ_1τ_2$-open set; weakly contra-$(τ_1,τ_2)$-continuous function